The Relationship Between Perceptions and Experiences of Diploma Nursing Students in Chronic Disease Patient Education in Community Settings: A Cross-Sectional Study - Sustiyono, Agus; Musfirowati, Fifi; Asra, Asra (Chakra Brahmanda Lentera Institute, 2026)
Background: The increasing burden of chronic diseases requires nurses to play an active educational role in empowering patients and supporting self-management. Therefore, nursing students must develop appropriate perceptions and gain practical experience in patient education. This study aimed to analyze the relationship between perceptions and experiences of Diploma Nursing students in providing chronic disease education in community settings. Methods: A quantitative cross-sectional study was conducted in accordance with the STROBE guidelines. The study involved 73 final-year Diploma Nursing students who had completed family and community nursing practice. Participants were selected using proportionate stratified random sampling. Students’ perceptions of patient education were treated as the independent variable, while their educational practice experiences were considered the dependent variable. Data were collected using a structured questionnaire with confirmed validity and reliability, and were analyzed using Pearson’s correlation test with a significance level of 0.05. Results: The majority of students demonstrated high perceptions regarding the importance of chronic disease patient education in community settings (76.8%) and reported favorable educational practice experiences (65.7%). Statistical analysis revealed a significant positive correlation between perceptions and experiences (r = 0.612; p < 0.001), indicating a moderate to strong association. Conclusion: Positive perceptions of the nurse’s educational role are associated with better educational practice experiences among Diploma Nursing students in community settings. These findings highlight the importance of strengthening community-based nursing education and integrating theoretical learning with practical patient education experiences to enhance students’ preparedness to function as effective health educators.